Trichinosis Caused by Ingestion of Raw Soft-Shelled Turtle Meat in Korea - Lee, Sang-Rok (The Korean Society for Parasitology and Tropical Medicine, 2013)
Reptiles, unlike mammals, have been considered to be unsuitable hosts of Trichinella spp., though larvae have been detected in their muscles and human outbreaks related to their consumption have, in fact, occurred. Herein we report 2 Korean cases of trichinosis, possibly transmitted via consumption of reptile meat. Both patients suffered from myalgia, headache, and facial edema. Laboratory examinations revealed leukocytosis with eosinophilia (54% and 39%, respectively) and elevated creatinine phosphokinase. ELISA was performed under the suspicion of trichinosis, showing positivity at the 29th and 60th day post-infection. Since they had consumed raw soft-shelled turtle meat, turtle was strongly suggested to be an infection source of trichinosis in Korea next to the wild boar and badger.